Investigation of a multiwavelength Raman fiber laser based on few-mode fiber Bragg gratings - Han, YG; Lee, SB; Moon, DS; Chung, Y (OPTICAL SOC AMER, 2005)
We propose and experimentally demonstrate a simple multiwavelength Raman fiber laser based on few-mode fiber Bragg gratings without additional multichannel filters. The multiwavelength Raman laser output has a high extinction ratio of more than 45 dB. The multiwavelength output is so stable that the peak power fluctuation is less than 0.5 dB. The number of lasing wavelengths can be adjusted, corresponding to the properties of few-mode Bragg gratings with multiple resonant wavelengths. By the thermal tuning method, the lasing wavelength of each channel can be effectively controlled, and the laser's tunability is measured to be 10.5 pm/degrees C. (c) 2005 Optical Society of America.